Fruitful Pederasty: Åsmund Sveen’s spiritual-vitalistic NS-Propaganda - Myren-Svelstad, Per Esben (Nordlit, 2022)
This article explores the contributions of the author Åsmund Sveen in the propaganda of the Norwegian Nazi party (NS). Earlier research on Sveen’s commitment to NS has had recourse to homophobic stereotypes in order to explain how a man living in a homosexual relationship could work for an ideology hostile to homosexuality. In this article, I consider the problem from the opposite perspective by instead asking how NS could accept Sveen’s inclusion of a homoerotic poem in a propaganda anthology of Norwegian literature. Reading Sveen’s propaganda in the light of a vitalist aesthetics and an ambiguous construction of masculinity, I argue that the relationship between homoeroticism and Nazism is a complex one in Sveen’s texts, but also in modern culture at large. Thus, a utopian vision of masculinity could be palatable to Nazi ideology.